EVALUATION OF ANATOMOPATHOLOGICAL, SEROLOGICAL, IMMUNOLOGICAL RESPONSES AND PROTECTION IN BROILERS VACCINATED WITH LIVE INFECTIOUS BURSAL DISEASE VACCINES - Nishizawa, M. [UNESP] (2022)
The study was divided into three experiments. In the first one, broilers were distributed into six groups and vaccinated against infectious bursal disease at 14 days of age: T1-not vaccinated, T2-Lukert1 (intermediate), T3-Lukert2 (intermediate plus), T4-228E, T5-V877 and T6-Winterfield 2512 (“hot” strains). Bursas of Fabricius (BF) were collected at 17, 21, 28 and 35 days to measure BF relative weight (BFRW), diameter, histological examination and image processing analysis (IPA). At one, 14, 21, 28 and 35 days of age, samples of blood taken from eight birds from each group for serology analysis by ELISA test. Hot strains vaccines induced reduction of BFRW and BF diameter, higher histological score lesion degree, more lymphocyte depletion on the BF follicles and higher IBD antibody titer. In the second experiment, 16 birds from groups T1 to T6 were isolated and challenged with a very virulent strain of IBDV (vvIBDV) at 25 days of age. Only groups T4, T5 and T6 were totally protected against vvIBDV challenge. In the third experiment, the immunosuppressive potential of each vaccine was determined by examining the ability of IBDVvaccinated birds to respond to Newcastle disease (ND) vaccination and challenge. None of the vaccines was found to be immunodepressive.